The Effect of E-Billing and E-Filing Implementation on Personal Taxpayer Compliance (Case Study at KPP Pratama Gorontalo) - Samuda, Wulan Ramadhanty; Blongkod, Harun; Taruh, Victorson (Syntax Corporation, 2023)
This study aims to determine the effect of the implementation of e-billing and e-filing on individual taxpayer compliance (a case study on KPP Pratama Gorontalo). This research method uses quantitative methods. The data used is primary data obtained by distributing questionnaires in the form of e-forms with the help of google forms quickly and widely through links to e-billing and e-filing users in Gorontalo Regency. The sampling in this study used the Yamane and Isaac and Michael formula so that the number of samples in this study amounted to 110. The analytical method used in this study was to use Structural Equation Model (SEM) Analysis with the help of the AMOS 24 program. The results showed that 1 ) The application of e-billing has a positive and significant effect on individual taxpayer compliance, 2) The application of e-filing has a positive and significant effect on individual taxpayer compliance.